Prevalence of livestock associated methicillin resistant Staphylococcus aureus (La-mrsa) in domestic livestock of Dharan, Nepal - Chaudary, Ayastha; Khanal, Hemanta; Sah, Shiv Nandan; Shrestha, Bijay Kumar; Chauhan, Sujata; Ghimire, Santoshi (Himalayan Journal of Science and Technology, 2023)
Introduction: Methicillin Resistant Staphylococcus aureus (MRSA) infection has drawn a lot of attention since studies suggested that animals may act as reservoirs for human infection. Over the past 20 years, MRSA infections have become more prevalent worldwide. MRSA was initially only discovered in humans, but later it was discovered in animals as well. Objectives: The study aimed to determine the prevalence of LA-MRSA in domestic livestock of Dharan, Nepal. Methods: Overall, 320 skin swab samples of cattle (cows) were collected by swabbing the skin of cattle aseptically with a sterile cotton swab and the samples were transported to the laboratory in a cold chain. The samples were streaked in Mannitol salt agar(MSA) containing oxacillin concentration of 6mg/L and incubated at 37°C for 24 hours. Staphylococcus aureus colonies were identified based on cultural characteristics on MSA plates (golden yellow colonies), Gram’s reaction, and positive results for coagulase and catalase test. The purified isolates of MRSA were subjected to antibiotic susceptibility tests and Biofilm formation. Results: MRSA was found to be prevalent in 10% of cattle. Antibiotic-resistant tests reported that MRSA was found to be sensitive to chloramphenicol 12(37.5%) followed by ceftriaxone 12 (37.25%), gentamycin 9(28.12%), cefotaxime 4(12.5%), while 100% of MRSA were resistant to penicillin and vancomycin. The moderate biofilm-forming MRSA was 5(15.625%), followed by 3(9.375%) weak biofilm producers and 24(75%) were negative towards biofilm formation. Conclusion: The prevalence of MRSA (10%) and Vancomycin-Resistant Staphylococcus aureus (100% VRSA) in cattle shows the need for regular surveillance. Chloramphenicol can be a treatment of choice for MRSA infections. However, emerging VRSA is a serious epidemiological issue that needs to be addressed properly. Therefore, Healthcare organizations must adopt precise criteria to control and prevent MRSA infection..